PENERAPAN MODEL TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN TEORI ATOM DI SMA PEMBANGUNAN PADANG - Asregi Asril (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Atomic Theory was one of learning materials delivered by discussion method. Discussion method was not make students more active in the learning process that caused student had low Minimum Completeness Criteria (KKM). One of learning strategies that could improve student activity was Teams Games Tournament (TGT) learning model type. This study aims to reveal the application of TGT learning model could increase percentage of student KKM in atomic theory in class XI IPA Development High School Padang. This type of research is an experiment by comparing the percentage of learning completeness with discussion method and with TGT. The population of this study was all students of class XI IPA Development High School Padang in the 2011/2012 academic year and the research sample was class XI IPA as an experimental class. Learning completeness by using TGT was 51.2% higher than discussion method that has 33.3% learning completeness. Therefore, there was an increase of learning completeness by 17.9% TGT. It means that learning chemistry using the Teams Games Tournament could increase the percentage of students' Minimum completeness criteria (KKM) on the atomic theory in class XI Padang Development High School.